The Effectiveness of Supported Decision-Making in Election for Persons with Disabilities in Indonesia - Juniar, Mutiah Wenda; Arini Nur Annisa; Ismail Iskandar; Nanda Yuniza; Wanda Anggraeni (Jurnal Mulawarman Law Review, 2024)
This research objective is to determine the effectiveness of implementing supported decision-making (SDM) in elections for persons with disabilities in Indonesia. Thus, there are two research questions: how is the current implementation of supported decision-making in Indonesia, and second, what are the issues Indonesia has encountered in implementing Supported Decision-Making (SDM), and what are the strategies to implement SDM effectively to fulfill the political rights of persons with disabilities in Indonesia. The research method is qualitative; we interviewed several relevant stakeholders to obtain primary data and used relevant literature and reports to obtain secondary data. Thus, the result of the research shows that currently, Indonesia has implemented SDM, which is known as guardianship, specifically for persons with intellectual and mental disabilities during the elections. However, several issues hamper the implementation, such as the lack of understanding or awareness from the families and providers regarding SDM, lack of regulations, and the dilemma of autonomy and secrecy. Thus, there must be some strategies to implement effective SDM, such as providing specific regulations on providing reasonable accommodation for election, providing training for the providers on the election, open accessible information to the public and persons with disabilities regarding SDM, and collaboration with Disabilities Organization.